A study of the blast wave shape from elongated VCEs. (November 2016) - Geng, Jihui; Thomas, Kelly; Baker, Quentin
Abstract: Elongated congestion patterns are common at chemical processing and petroleum refining facilities due to the arrangement of processing units. The accidental vapor cloud explosion (VCE) which occurred at the Buncefield, UK facility involved an elongated congested volume formed by the trees and undergrowth along the site boundary. Although elongated congested volumes are common, there have been few evaluations reported for the blast loads produced by elongated VCEs. Standard VCE blast load prediction techniques do not directly consider the impact of this congested volume geometry versus a more compact geometry. This paper discusses an evaluation performed to characterize the blast loads from elongated VCEs and to identify some significant differences in the resulting blast wave shape versus those predicted by well-known VCE blast load methodologies (e.g., BST and TNO MEM). The standard blast curves are based on an assumption that the portion of the flammable gas cloud participating in the VCE is hemispherical and located at grade level. The results of this evaluation showed that the blast wave shape for an elongated VCE in the near-field along the long-axis direction is similar to that for an acoustic wave generated in hemispherical VCEs with a low flame speed. Like an acoustic wave, an elongated VCE blast wave has a very quick transition from the positive phase peak pressure to the negative phase peak pressure, relative to the positive phase duration. The magnitude of the applied negative pressure on a building face depends strongly on the transition time between the positive and negative phase peak pressures, and this applied negative phase can be important to structural response under certain conditions. The main purpose of this evaluation was to extend previous work in order to investigate how an elongated VCE geometry impacts the resultant blast wave shape in the near-field. The influence of the normalized flame travel distance and the flame speed on the blast wave shape was examined. Deflagration and deflagration-to-detonation transition regimes were also identified for unconfined elongated VCEs as a function of the normalized flame travel distance and flame speed attained at a specified flame travel distance. Highlights: An evaluation was performed to characterize the blast loads from elongated VCEs. Elongated VCE blast wave shape is similar to that for an acoustic wave. Elongated VCE blast wave has a very quick transition from the positive to the negative phase peak pressure. Outside the congested cloud end, the magnitude of the pressure drop diminishes quickly with distance. Deflagration and deflagration-to-detonation transition regimes were identified.